PENGETAHUAN DAN PERSEPSI PETANI TERHADAP PENGOMPOSAN LIMBAH JERAMI PADI - Nengah, Muliarta (Jurnal AGRISEP, 2021)
The utilization of rice straw as compost is very related to farmers' knowledge on how to compost agricultural waste. Knowledge of rice straw composting owned by farmers is closely related to socialization and training obtained from field extension officers (FEO). The role of FEO in the field becomes very strategic in an effort to increase farmers' knowledge about agricultural waste treatment and its utilization so as to provide economic impact. The purpose of the research is to understand the knowledge and perception of farmers about composting rice straw. By using survey and interview methods, this research also seeks to uncover farmers' knowledge related to rice straw compost. The research was conducted in 3 sub-districts in Klungkung (Klungkung, Dawan, and Banjarangkan) during May-June 2017. The results showed that farmers do not know how to compost rice straw because only 2.25% of farmers have ever attended rice straw composting training. Dominant farmers (74.16%) view if rice straw cannot be composted. The results of interviews with FEO in the Klungkung district obtained the fact that FEO never socialized rice straw composting.